IMPROVEMENT OF UNIVERSITIES’ COMPETITIVENESS: ATTRACTION OF NON-STATE FUNDS - Rodinova, Nadezhda; Romagna, Inna; Ostroukhov, Vladimir; Bereznyakovsky, Vladimir; Grunina, Alexandra (Revista Inclusiones, 2019)
In the article, the authors analyze the main tendencies in the formation of universities’ financial autonomy. Alternative funding sources for universities have been determined. It has been established that the correct organization of the financial structure and universities’ expansion of the areas for the attraction of funds will contribute to improving their competitiveness.